Factors that influence social media marketing adoption among Muslim SMES at Malacca City / Dayana Mohd Ramli and Nur Hafifah Mohd Hamzah - Mohd Ramli, Dayana; Mohd Hamzah, Nur Hafifah (Faculty of Business Management, 2016)
Applications such as social media in the business environment have profound profit implications. Large companies around the globe have invested much of their resources to incorporate social media applications as an important marketing tool to reach their customers. Cost reduction, increase capability, communication improvement and customer service improvement are among the benefits perceived by these companies. However, the practice of web-based marketing among small and medium enterprises (SMEs) in Malaysia is still in its infancy. This study intends to investigate the factors that influence social media marketing adoption among Muslim SMEs at Malacca City. Therefore, there are four determining factors which are security, ease of use, management’s attitude and general knowledge constitute the central focus of the theoretical framework in this study. A quantitative survey was developed to gather data from 78 Muslim SMEs employees in Malacca Tengah in relation to factors that would influence social media marketing adoption among Muslim SMEs. Findings from this study revealed that the proposed framework could be used to understand the factors influencing social media marketing adoption by Muslim SMEs in Malacca City.